Performance of Severe Acute Respiratory Syndrome Coronavirus 2 Antibody Assays in Different Stages of Infection: Comparison of Commercial Enzyme-Linked Immunosorbent Assays and Rapid Tests. (30th May 2020) - Traugott, Marianna; Aberle, Stephan Walter; Aberle, Judith Helene; Griebler, Hannah; Karolyi, Mario; Pawelka, Erich; Puchhammer-Stöckl, Elisabeth; Zoufaly, Alexander; Weseslindtner, Lukas
Abstract: We comparatively assessed sensitivities and specificities of 4 commercial enzyme-linked immunosorbent assays (ELISAs) and 2 rapid tests in 77 patients with polymerase chain reaction–confirmed severe acute respiratory syndrome coronavirus 2 infection, grouped by interval since symptom onset. Although test sensitivities were low (<40%) within the first 5 days after disease onset, immunoglobulin (Ig) M, IgA, and total antibody ELISAs increased in sensitivity to >80% between days 6 and 10 after symptom onset. The evaluated tests (including IgG and rapid tests) provided positive results in all patients at or after the 11th day after onset of disease. The specificities of the ELISAs were 83% (IgA), 98% (IgG), and 97% (IgM and total antibody). Abstract : Comparison of commercial enzyme-linked immunosorbent assays in severe acute respiratory syndrome coronavirus 2 infection shows low test sensitivities within 5 days after disease onset. Immunoglobulin (Ig) M and IgA test performances increase thereafter, with positivity rates of 100% during the late phase of the infection (including IgG tests).